STRATEGI KOMUNIKASI POLITIK TIM PEMENANGAN DEDI & TOPANI PADA PILKADA 2024 KABUPATEN PESISIR BARAT PROVINSI LAMPUNG - Irfan Nurudin; Nadirsah Hawari; Gesit Yudha (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
The 2024 Regional Head Election (Pilkada) in Pesisir Barat Regency reveals a gap between the relatively balanced parliamentary support of the candidate pairs and the final vote results. Despite similar levels of party backing, the election outcomes show significant differences in vote result, raising questions about the role of political communication strategies in influencing voter preferences. This study aims to analyze the political communication strategy implemented by the campaign team of Dedi Irawan and Irawan Topani in navigating the competition of the 2024 Pesisir Barat Pilkada. This research employs a qualitative approach with a descriptive design. The data consist of primary and secondary sources. Primary data were obtained through in-depth interviews with the Secretary of the Dedi & Topani Campaign Team, members of rival campaign teams, and election organizers. Secondary data were collected from official KPU documents, election regulations, and relevant literature on political strategy and communication. The findings indicate that the political communication strategy of the Dedi & Topani campaign team was not rigidly based on initial planning but evolved dynamically in response to field conditions. Within the framework of strategy as plan, the team conducted mapping of political strengths, vote distribution areas, and potential threats down to the polling station level as the basis for field operations. Through strategy as ploy and strategy as pattern, the team managed issues related to bureaucratic neutrality, clarified public perceptions regarding social assistance programs, and implemented repetitive face-to-face campaign activities. In terms of strategy as position, Dedi & Topani were framed as symbols of change, with a particular focus on young voters. Meanwhile, strategy as perspective was reflected in the team’s internal worldview that interpreted political competition as an opportunity to build public awareness of the need for change. This communication strategy has led to increased political understanding among some members of the community, although regional election outcomes are often influenced by local power dynamics, political resources, and a pragmatic political culture.